Meesha makes friends - Percival, Tom, 1977- (Percival, Tom, 1977- Big bright feelings., 2021)
"Meesha doesn't know quite what to do, what to say, or when to say it, and she struggles reading and responding to social cues. But one day, she discovers that she has a special talent that will help her navigate challenging social situations and make friends." --